2022
DOI: 10.4269/ajtmh.22-0059
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity during COVID-19 in Yemen

Abstract: ABSTRACT. The United Nations has declared Yemen as the world’s worst humanitarian crisis with 21 million people in need of humanitarian assistance. Due to the convergence of severe economic instability exacerbated by the COVID-19 pandemic, stifling war, and spiking food prices, the Yemeni people are at the brink of famine with women and children especially malnourished. Desperate to feed their families, civilians are forced to resort to begging, participate in child marriages, or plunge into debt. An inflated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…, 2022). The COVID-19 pandemic has caused food security in Yemen, a war-torn nation that has been coping with a food crisis even before the pandemic (Rahmat et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022). The COVID-19 pandemic has caused food security in Yemen, a war-torn nation that has been coping with a food crisis even before the pandemic (Rahmat et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In Yemen, the COVID-19 case was initially announced on April, 10th 2020 and has caused 592 deaths out of 2045 infected people on October 5th that year (Kotiso et al, 2022). The COVID-19 pandemic has caused food security in Yemen, a war-torn nation that has been coping with a food crisis even before the pandemic (Rahmat et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Referring to politically fragile countries (e.g., Lebanon, Sudan, and Yemen) in the context of the ongoing conflict in Ukraine, Al-Saidi [44] proposes that a combination of political-economic instability, constrained domestic agriculture, and inadequate reliable grain reserves have exacerbated the existing food crisis in certain countries. Indeed, the pandemic exacerbated pre-COVID-19 crises in several countries of the MENA region [45], such as Syria [46], Iraq [46], Yemen [47], Palestine [48], and Lebanon [49]. In this respect, the Arab Forum for Environment and Development [50] suggests that existing issues have made Arab nations much more exposed to the regional implications of both the COVID-19 pandemic and the conflict in Ukraine.…”
Section: Sourcementioning
confidence: 99%
“…More than 50% of Yemen's population had to face hunger in 2021 (Hashim et al, 2021). Around 90% foods are imported, and Norwegian Refugee Council reported that more than 90% families have cursed COVID-19 for food and other necessity inflation (Rahmat et al, 2022).…”
Section: Arab and Middle East Unrestmentioning
confidence: 99%